Irrigation suitability mapping examples from Zimbabwe, Zambia, Malawi and Kenya - Mabhaudhi, Tafadzwanashe; Haileslassie, Amare; Magidi, J.; Nhamo, L. (International Water Management Institute (IWMI), 2022)
The irrigation suitability classification was achieved by using physical factors that include slope, rainfall, landuse, closeness to waterbodies (surface and groundwater) and soil characteristics for selected districts in Zimbabwe, Zambia, Malawi, and Kenya, some of the UU target countries. As cereals form the main food basket of the selected countries, and cereals are not tolerant to saline conditions, the report also provides maps showing high soil salinity areas of Makueni and Nakuru of Kenya, where soils are highly saline. However, soil salinity is insignificant in the other study districts and therefore not mapped. This report provides (a) a conceptual framework and detailed methodology for irrigation suitability mapping, including details of identified boundary maps and geospatial data, and (b) a synthesis model and maps on irrigation suitability mapping for the selected districts in the four target countries.